Stroke outcome of early antiplatelet in post-thrombolysis haemorrhagic infarction. Issue 8 (26th April 2022) - Zhong, Wansi; Yan, Shenqiang; Chen, Zhicai; Luo, Zhongyu; Chen, Yi; Zhang, Xuting; Wu, Chenglong; Tang, Weiguo; Zhang, Xiaoling; Wang, Yaxian; Gu, Qun; Xu, Dongjuan; et al.
Abstract : Background and purpose: Initiation of early antiplatelet (EA) therapy after acute ischaemic stroke (AIS) is essential. We aimed to investigate the safety and effectiveness of EA therapy in patients who had an AIS with haemorrhagic infarction (HI) after intravenous thrombolysis (IVT). Methods: Based on a multicentre stroke registry database, patients who had an AIS with post-thrombolysis HI at 24 hours were identified. EA users and non-EA users were defined as patients with HI who received or did not receive antiplatelet therapy between 24 and 48 hours after IVT. Primary outcome was favourable outcome defined as modified Rankin Scale scores 0–2 at 3 months. Secondary outcomes were early neurological deterioration (END) and haemorrhagic transformation expansion. Results: A total of 842 patients with HI were identified from 24 061 thrombolytic patients within 4.5 hours, and 341 (40.5%) received EA therapy. EA users were more likely to have a favourable outcome (55.7% vs 39.5%, OR 1.565; 95% CI 1.122 to 2.182; p=0.008) and lower rate of END (12.6% vs 21.4%, OR 0.585; 95% CI 0.391 to 0.875; p=0.009) compared with non-EA users. EA therapy was not associated with haemorrhagic transformation expansion (p=0.125). After propensity score matching, EA therapy was still independently associated with favourable outcome (54.3% vs 46.3%, OR 1.495; 95% CI 1.031 to 2.167; p=0.038) and lower risk of END (13.5% vs 21.2%, OR 0.544; 95% CI 0.350 to 0.845; p=0.007). Conclusions: Antiplatelet therapy can be safely used between 24 and 48 hours when HI occurs after IVT, and such therapy is associated with reduced risk of END and improved neurological outcome in patients who had an AIS.